Exploring Perceived Family Distress and Negative Emotional States among Indonesian Adolescents - Rahmandani, Amalia; Franz La Kahija, Yohanis; Sakti, Hastaning; Nur Ardhiani , Lusi (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Mental health problems related to negative emotional states are important factors in adolescents’ development. Perceived family distress can be considered as one of the contributing factors. This study aims to describe the perceived family distress of Indonesian adolescents and its association with negative emotional states. Methodology: A total of 909 Indonesian students from a public vocational high school were involved in this study (MAge=15.93; SDAge=.909; male=60.3%; female=39.7%). The Brief Family Distress Scale was used to measure perceived family distress, whereas negative emotional states was measured with the Depression Anxiety Stress Scale. Analysis was conducted with descriptive (by using crosstabs) and inferential statistics (both correlational and comparative). Results: The results of categorization of perceived family distress (M=2.36; SD=1,695) showed that 83.1% were in the "no impairment", 9.2% in the "moderate impairment", and 7.8% in the “marked impairment”. Sex, parents’ marriage status, and live mate predicted perceived family distress. Perceived family distress was positively related to depression, anxiety, and stress. The increasing degree of perceived family distress was followed by the decrease in the percentage of subjects. But the majority of subjects at each level of family distress still had a normal negative emotional state. Applications/Originality/Value: These results add to the description of perceived family distress among adolescents with collectivistic culture, especially from Indonesia. They can be considered by researchers in future studies focused on family distress and mental health, and practitioners in future interventions that help minimize the impact of perceived family distress to achieve optimal mental health.